ANALISIS KINERJA BERBASIS KEPUASAN KERJA DAN KOMPENSASI DENGAN VARIABEL INTERVENING MOTIVASI KERJA - Wahyu Sediarsih (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
The aim of this research was to analyze the effect work satisfaction and compensation with work motivation as intervening variable towards work performance of insurance installation’s employee at RSUP dr. Sardjito.  The result was based the first hypothesis was accepted, so the Second Hypothesis was rejected, the Third Hypothesis was accepted, the Fourth Hypothesis was rejected, the Fifth Hypothesis was rejected, so the Sixth Hypothesis was rejected, so the Seventh Hypothesis was rejected. To be concluded: 1) Work satisfaction had positive and significant result towards work motivation; 2) Compensation has positive result yet insignificant towards work motivation; 3) Work satisfaction and compensation had positive and significant result towards work motivation; 4) Work satisfaction had positive yet insignificant result towards work performance; 5) Compensation had negative and insignificant result towards work performance ; 6) Work motivation had positive yet insignificant result towards work performance; 7)  Work satisfaction, compensation, and work motivation affected each other, but insignificant towards work performance. Keyword: The Work Performance Analysis, The Work Satisfaction, Compensation, Motivation.